Revelieria groehni — a New Species of Minute Brown Scavenger Beetles (Coleoptera, Latridiidae) from Baltic Amber - Sergi, T.A.; Perkovsky, E.E.; Reike, H.-P. (Вестник зоологии, 2013)
Based on a fossil specimen from Late Eocene Baltic amber, Revelieria groehni Sergi, Perkovsky et Reike, sp. n., a new species is described. It is the first fossil species of the genus Revelieria Perris, 1869. The new species clearly differs from extant R. californica and R. genei in the following characters: eyes more large and convex; antennal insertion located more close to eye; temples very short; metasternum longer; fore tibia evenly curved inwards. Из позднеэоценового балтийского янтаря описан Revelieria groehni Sergi, Perkovsky et Reike, sp. n. Это первый ископаемый вид рода Revelieria Perris, 1869. Новый вид отличается от современных R. californica и R. genei следующими признаками: глаза более крупные и выпуклые; усиковые впадины расположены ближе к глазу; виски очень короткие; заднегрудка длиннее; передняя голень равномерно изогнута внутрь.